HUKUMAN PELAKU PERKOSAAN DIBARENGI PEMBUNUHAN OLEH ANAK DITINJAU DARI HUKUM POSITIF DAN HUKUM ISLAM (Study Analisis Keputusan Pengadilan Negeri Curup Nomor 7/Pid.Sus.Anak/2016/Pn.Crp) - Heriansyah, Heriansyah (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
This research  raises the issue of punishment imposed by the judges on Curup  District Court  Number  7 / Pid.Sus. Anak / 2016  / PN.Crp  to the child as the perpetrator of rape  accompanied by the murder  of the child victim. The purpose of this research  is to know the punishment and  basic consideration of judges panel  then  reviewed  from positive law and  Islamic law. This research  uses normative juridical legal method, with approach of Act, case approach and  conceptual approach. The method of collecting legal material  used  is literature  study  and  documentary study  then  analyzed  by normative descriptive. From the results of research  shows that the implementation of criminal punishment for perpetrators of rape coupled  murder  of children  in terms of positive law can be implemented by the panel  of judges by applying  Article 81 paragraph (1) of Law RI.35 Year 2014  About Amendment to Law no. 23 of 2002  in conjunction with Article 76D of RI Law. 35 of 2014  on Amend- ment to Law No. RI. Article 55 Paragraph (1) and (2) of the Indonesian Criminal Code  and Article 80 Paragraph (3) of RI Law No. 23 Year 2002  on Child Protection jo Article 55 Paragraph (1) of the Criminal Code  jo Article 65 Paragraph (1) and  (2)35 Year 2014  About Amendment to Law no. Law No. 23 Year 2002  on the Protection of Children  in conjunction with Article65 Paragraph (1) and  (2) of the Criminal Code  are cumulative. Whereas  in Islamic law the perpetrator may be subjected to a more  severe  crime (murder)  which is the murder  in which the perpetrator is assumed to have  committed  intentional  murder with the punishment of the principal in the form of diat and  kafarat, the substitution  of ta’zir and  the additional punishment of the inheritance and  will. Based  on the decision of the Curup  District Court Number  7 / Pid.Sus.Anak / 2016  / PN.Crp  that the perpetrators of rape are found to have proven  legally and convincingly guilty of intercourse with him or with others and place, let, participate in violence against children who causing the child to die so that the imprisonment is imposed for 10 (ten) years and  the training of each  work for 6 (six) months.  According to Islamic law the offender  may be punished by paying  diyat to the heirs of 100 (one hundred) camels or 200 (two hundred) cows or 2000  (two thousand) goats, freeing a slave or fasting two months  in a row and ta’zir